ANALISIS PENERAPAN E-FILING PADA WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA BITUNG - Meisiang, Yuyun; Sondakh, Jullie J.; Warongan, Jessy D.L (Universitas Sam Ratulangi, 2018)
To increase state tax revenue, the Directorate General of Taxes conducts administrative reforms in the field of taxation by implementing e-Filing, a means of reporting on Annual Individual Income Tax Returns online. The application of e-Filing is expected to facilitate Taxpayers to carry out tax obligations so as to increase state revenues. This study aims to analyze the application of e-Filing to Individual Taxpayers at Bitung Primary Tax Office. The sampling method in this study is a descriptive qualitative approach using primary and secondary data through observation of interviews with tax officers and individual taxpayers registered at the Bitung Primary Tax Office. The results of this study indicate that the implementation of e-Filing has not been effective enough, the number of Individual Taxpayers who used e-Filing in 2016 was 32,374 taxpayers, and there was a decline in 2017 of 29,477 taxpayers. The application of e-Filing will be maximum if the KPP Pratama Bitung increases socialization.Keywords : E-Filing, implementation of e-filing, personal taxpayer